Conductive Hybrid Cu‐HHTP‐TCNQ Metal–Organic Frameworks for Chemiresistive Sensing (Adv. Electron. Mater. 3/2022). (10th March 2022) - Lüder, Lars; Gubicza, Agnes; Stiefel, Michael; Overbeck, Jan; Beretta, Davide; Sadeghpour, Amin; Neels, Antonia; Nirmalraj, Peter N.; Rossi, René M.; Toncelli, Claudio; Calame, Michel
Abstract : Metal‐Organic Framework Film In article number 2100871, Lars Lüder, Michael Calame, and coworkers present a metal organic‐framework film, which shows good electrical conductivity and basic chemiresistive response towards ambient environmental changes, originated by the interaction between the analytes and the metal organic‐framework when entering the framework's pores. Thus, this framework illustrates a potentially good application of framework architectures for future chemiresistive sensing devices.